Estimation Earthquake Source Parameters in Mentawai Island Region Using Moment Tensor - Husna, Fahmia Zuwidhatul; Sungkono, Sungkono; Fahmi, Muhammad Nurul; Minarto, Eko; Saifuddin, Saifuddin (Jurnal Fisika dan Aplikasinya, 2025)
Mentawai Islands is a seismically active zone that often experiences earthquakes due to the interaction of tectonic plates, so it is necessary to analyze the earthquake source parameters to understand its characteristics. This research aims to determine the earthquake source parameters in the Mentawai Islands in 2023 for earthquakes with magnitude Mw ≥ 5.5. Three-component waveform data from GEOFON network is used for moment tensor inversion process in time domain. Waveform data used in the frequency range of 0.01 to 0.025 Hz with a match value of calculation and observation data worth >70%. The results of waveform data analysis show that the earthquake in the study area was caused by tectonic activity characterized by the percentage of Double-Couple (DC) more dominant than Compensated Linear Vector Dipole (CLVD), with shallow depth. In addition, the focal mechanism of the waveform data analysis indicates that the type of fault that causes the earthquake in the study area is a reverse fault. This result is consistent with earthquake catalogs (GCMT, USGS, and GFZ).